The Relationship Between Inhibiting Factors and the Implementation of the Occupational Safety and Health Management System - Sri Wahyuni Nasution; Shefira Aprilia; Chrismis Novalinda Ginting (Jurnal Penelitian Pendidikan IPA, 2023)
Occupational health and safety in hospitals is influenced by Occupational Safety and Health Management System or what is often called SMK3 which functions to regulate occupational safety and health in an industry or building. This research aims to analyze the relationship between inhibiting factors and the implementation of the occupational health and safety management system at the Royal Prima Medan Hospital. This research is an analytical survey research using a cross sectional study design carried out in June 2023. The sample in this research is all medical personnel who work in Royal Prima Medan Hospital, namely 121 people. The sample size is determined using the total population formula. Data were analyzed using the chi square test and logistic regression. The research results show that there is a relationship between HR quality, HR workload, HR work environment, wage levels and the rate of addition of new workers with the implementation of the occupational safety and health management system at the Royal Prima Medan Hospital. The most dominant variable related to the implementation of the occupational safety and health management system at the Royal Prima Medan Hospital is the wage level. It is recommended to the hospital that the results of this research can be used as input to improve and develop the level of occupational health and safety, especially for hospital workers, which can also indirectly improve the quality of service and work productivity of the hospital